NUTRITIONAL STATUS AND ITS ASSOCIATION WITH THE DEVELOPMENT OF TODDLER IN THE WORKING AREA OF PUSKESMAS BLANG KUTA, PIDIE JAYA - Intan Mastura; Nurlaili Ramli; Nurlaila Ramdhan (Department of Midwifery, Health Polytechnic of Aceh, 2022)
Introduction: Toddlerhood is a very important period of life and needs serious attention. At this time, a very rapid growth and development process occurs, such as physical growth and psychomotor, mental and social development. One of the important factors that affect the growth and development of toddlers is nutritional status. Malnutrition in children will have an impact on faltering growth, susceptibility to infection and child development hindrance. Method: This study was conducted using an analytical survey with a cross sectional approach in the working area of ​​ Puskesmas Blang Kuta Pidie Jaya from January to February 2019. The sample used in this study were children from the age of 1 to 5 years in Puskesmas Blang Kuta Pidie Jaya working area who met the inclusion criteria with a total sample of 85 toddlers. As the multistage sampling technique was used which consisting of purposive sampling, stratified random sampling, and accidental sampling. Result: There were 77 toddlers with good nutritional status (90.6%), and 8 toddlers with poor nutritional status (9.4%). Appropriate development of toddlers has a total number of 12 toddlers (14.1%), dubious with 24 toddlers (28.2%) and deviation with 49 toddlers (57.7%). Kendall-Tau test showed 0.227. Conclusion: There was no association between nutritional status and the development of toddlers from the age of 1 to 5 years in the working area of ​​ Puskesmas Blang Kuta. Health care workers were expected to do growth and development monitoring on a regular basis.